An N-annulated perylene butyl tetraester for alcohol processed semiconducting organic thin films. (1st December 2022) - Wolfe, Kathryn M; Mooney, Madison; Crep, Chloe; Rondeau-Gagné, Simon; Welch, Gregory C
Abstract: Herein, we report on the design and synthesis of an N-annulated perylene butyl tetraester (PTEN-H) for use in alcohol processed semiconducting films. PTEN-H was contrasted with the known N-annulated perylene diimide (PDIN-H) where the former has ring-opened imide positions which in turn lowers the electron affinity (i.e. rendering hole transporting) and improves polar green solvent solubility. PTEN-H can be solubilized in 1-butanol up to 10 mg ml −1 with gentle heating and can be spin-cast or slot-die coated to form uniform thin films on glass and/or plastic substrates. Organic field-effect transistors (OFETs) were fabricated using PTEN-H in the active material layer which was deposited from solution using 1-butanol as the solvent. While hole mobilities were achieved (0.39 × 10 −4 cm 2 Vs −1 ), blending the molecular material with a previously reported green solvent processable semiconducting polymer, IIG20-OH, was done to boost performance. This led to increased mobilities for not only the native molecular PTEN-H material, but for the native IIG20-OH polymer as well. Furthermore, a blend of PTEN-H and IIG20-OH were slot-die coated onto a polyethylene terephthalate (PET) substrate giving uniform thin films suitable for large area device fabrication.